PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HOTS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPS UNTUK SISWA SEKOLAH DASAR - Putri Gupurli; Yohana Satinem; Andri Valen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop a hots-based student worksheet using a problem model based learning. Testing the validity, practicality and effectiveness of hots-based student worksheets using the problem based learning model in social studies learning at State Elementary School 25 Lubuklinggau. This type of research is Research and Development with a model ADDIE development. The subjects of this research were class V students at SD Negeri 25 Lubuklinggau. Data collection techniques use observation, interviews, questionnaires, tests and documentation. Based on the results of the validity of student worksheets by language, materials and media experts indicate that the student worksheets are satisfactory valid criteria with an average score of 0.88. Meanwhile, from the assessment sheet The practicality of teachers and students is that students' worksheets are hots-based using a problem model based learning meets practical criteria with an average score of 93.5%. On test the large group obtained an N-gain (g) of 0.71 with a high classification, which This means that hots-based student worksheets using the problem based learning model are effective which is being. Based on the writing results, it can be concluded that the worksheet Hots-based students using the problem based learning model have been proven to be valid, practical and effective, in social studies learning for fifth grade elementary school